KEDUDUKAN PARA PIHAK DALAM PERJANJIAN KERJASAMA OPERASIONAL PENGEMBANGAN LAHAN PERUMAHAN DAN IMPLIKASINYA TERHADAPHAK PENGELOLAAN LAHAN - Sawitri, Galuh (Notarius, 2018)
AbstractÂ The unity of PT Pradipta Ratnapratala as the owner of the asset with PT Citra Mitra Properti (Ciputra Group) as investor in the Land Development Cooperation Agreement gave birth to a new business entity entity by the parties named "Citra Pradipta KSO".. The formulation of issues that can be stated is the legal standing of the parties in the Cooperation of Cooperation Agreement / KSO of Land Development, how the implications of the legal status of the parties to the right of land management and whether efforts can be made to the rights and obligations of the parties in the operational cooperation agreement to be balanced and equivalent. The research used empirical juridical approach method with qualitative data analysis. The result of this research is the position of the parties in the Cooperation Agreement of Land Development Cooperation, namely PT Pradipta Ratnapratala as the holder of the land of cooperation / as the owner of the asset tends to passive, which then affects the loss of PT Pradipta Ratnapratala's right as the owner of the rightful owner or the right land of cooperation land, to be involved in the implementation process of housing project development. Efforts that can be made is to improve and / or add clauses in the agreement and include the owner of the asset in the operational activities of land development, although in practice the authority will be given with certain limitations..Â AbstrakÂ Bersatunya PT Pradipta Ratnapratala selaku pemilik asset dengan PT Citra Mitra Properti (Ciputra Grup) selaku investor dalam Perjanjian Kerjasama Pengembangan Lahan melahirkan sebuah entitas pelaku usaha baru yang oleh para pihak diberi nama â€œCitra Pradipta KSOâ€.Rumusan masalah yang dapat dikemukakan adalah kedudukan hukum para pihak dalam Perjanjian Kerjasama Operasional/ KSO Pengembangan Lahan, bagaimana implikasi dari kedudukan hukum para pihak tersebut terhadap hak pengelolaan lahan serta apakah upaya yang dapat dilakukan agar hak dan kewajiban para pihak dalam perjanjian kerjasama operasional menjadi seimbang dan setara. Penelitian menggunakan metode pendekatan yuridis empiris dengan analisa data kualitatif.Hasil penelitian ini adalah kedudukan para pihak dalam Perjanjian Kerjasama Operasional Pengembangan Lahan yaitu pihak PT Pradipta Ratnapratala selaku pemegang hak atas tanah lahan kerjasama/selaku pemilik asset cendrung pasif, yang kemudian berdampak pada hilangnya hak PT Pradipta Ratnapratala selaku pemilik asset atau pemegang hak yang sah terhadap tanah lahan kerjasama, untuk ikut terlibat pada proses pelaksanaan pembangunan proyek perumahan. Upaya yang dapat dilakukan adalah memperbaiki dan/atau menambahkan klausul-klausul dalam perjanjiandan mengikut sertakan pihak pemilik asset dalam kegiatan operasional pengembangan lahan, walaupun dalam pelaksanaannya kewenangan tersebut akan diberikan dengan batasan tertentu.Â